GOOD CORPORATE GOVERNANCE DAN TAX AVOIDANCE PADA PERUSAHAAN MULTINASIONAL DALAM MODERASI PENINGKATAN TAX AUDIT COVERAGE RATIO - Nanda Widiiswa, Ryan Agatha; Baskoro, Randy (Scientax, 2020)
Post 1998 economic crisis era, Good corporate governance (GCG) or "Tata Kelola Perusahaan yang Baik" emerged as a guideline for companies in Indonesia. This guideline promotes responsible business practices regarding three aspetcs: economic, social, and legal (including tax liability). This research seeks to the effect of applying GCG to tax avoidance on multinational companies, and analyzes how the increase of tax audit coverage ratio as a variable that moderates this relationship. The author analyses how the strenghtening tax policy during the period of 2014-2017 affects the relationship of the application of GCG on multinational companies to tax avoidance. This is a quantitative research by applying descriptive statistical analysis and regression analysis. This research aims to provide an overview to policy makers in understanding the effect of increasing tax audit coverage ratio to taxpayers’ behaviour in implementing GCG associated with tax avoidance.